Blue hydrogen and carbon nanotube production via direct catalytic decomposition of methane in fluidized bed reactor: Capture and extraction of carbon in the form of CNTs. (15th March 2021) - Parmar, Kaushal R.; Pant, K.K.; Roy, Shantanu
Graphical abstract: Highlights: Blue hydrogen was produced by the catalytic decomposition of methane. A 60%Ni-5%Cu-5%Zn/Al2 O3 catalyst was prepared and used for H2 and CNT production. An ultrasonication process was used for CNT separation. Multiple reaction-regeneration cycles were performed. 3D Raman mapping was utilized to characterize and estimate the quality of CNTs. Abstract: The current study reports a regenerative approach for producing blue hydrogen (COx -free) and carbon nanotubes (CNTs) from natural gas (methane). The multi-metallic nickel-based copper and zinc promoted catalyst with an optimal composition (60%Ni-5%Cu-5%Zn/Al2 O3 ) was synthesized in the laboratory and used for the pyrolysis of methane in a fluidized bed reactor under bubbling conditions. Fluidized bed reactor hydrodynamics and CNT extraction were well-thought-out while designing the catalyst. The separation of the CNTs and partial regeneration of the spent catalyst was performed using the ultrasonication technique. The regeneration ability of the catalyst was examined by performing multiple reaction-regeneration cycles. The regenerated catalyst regained its full activity, and >90% methane conversion was achieved with high-quality CNTs (o.d 60–80 nm, length 5 μm). State-of-the-art characterization tools like 3D-Raman mapping, high-resolution electron microscopy, EDX mapping were utilized to analyze CNTs. 3D-Raman map consists of 29, 200 spectra ensured the uniformity and purity of grown CNTs.